Association between chronic pain and long-term cognitive decline in a population-based cohort of elderly participants. Issue 2 (February 2021) - Rouch, Isabelle; Edjolo, Arlette; Laurent, Bernard; Pongan, Elodie; Dartigues, Jean-François; Amieva, Hélène
Abstract : Abstract: Chronic pain (CP) was associated with impaired cognitive performance in several cross-sectional studies conducted in older adults; however, fewer longitudinal studies assessed this link that remains still debated. With a prospective design, the present analysis was aimed at evaluating the relationship between CP and the change in several tests assessing memory, attention, verbal fluency, and processing speed. The study population was selected from the PAQUID study, a cohort of community dwellers aged 65 years and older; 693 subjects receiving a pain assessment were included. Chronic pain was evaluated using a questionnaire administered at 3-year follow-up. Cognitive performances were assessed every 2 to 3 years between 3 and 15 years assessing general cognition (Mini-Mental State Examination), verbal and visual memory (word paired-associate test and Benton test), attention and speed processing (Wechsler Digit Symbol Substitution Test and Zazzo's Cancellation Task), and language skills and executive functions (Isaacs Set Test). The link between CP and the change in cognitive function was assessed with latent process mixed models controlled for age, sex, education, comorbidities, depression, and analgesic drugs. The association between CP and each of the cognitive scores was then tested with the same procedure. A significant relationship was observed between CP and poorer 15-year scores on global cognitive performance ( P = 0.004), and specifically, the Digit Symbol Substitution Test ( P = 0.002) was associated with a higher slope of decline ( P = 0.02). Chronic pain is associated with a higher cognitive decline, particularly in processing speed. This result reinforces the importance of actively treating CP with pharmacological and nonpharmacological strategies to prevent its consequences, including cognitive consequences. Abstract : Supplemental Digital Content is Available in the Text.The presence of chronic pain is associated with a higher cognitive decline in the elderly, particularly in processing speed.